The nurse's role in preventing SARS-CoV2 infections in the operating room during the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: The present study aims to describe, from the analysis and review of the literature, the role of health professionals in preventing infections by SARS-CoV2 in the operating room during the COVID-19 pandemic. Methodology: This is an integrative literature review, descriptive based on studies published in the periods from 2016 to 2021. The integrative review is a study that determines knowledge about the specific theme, this study is conducted to identify, analyze and synthesize results of independent studies on the subject, contributing to quality in the scope of the research. Results: Through the Descending Hierarchical Classification (CHD) the IRAMUTEQ software recognized 138 text segments (ST) in this research and maintained 98 of these segments, obtaining a total of 71.01% of utilization. Thereafter, the corpus was divided into 6 classes, in which class 1 corresponds to 16.3% of words in the corpus, class 2 corresponds to 18.4%, class 3 corresponds to 14.3%, class 4 corresponds to 21.4%, class 5 corresponds to 14.3% and class 6 corresponds to 15.3%. Final considerations: The role of nursing in this context is indisputable, as it is one of the professions in which there is greater contact with patients and, in this sense, it is important that they carry out specific measures to prevent the spread of microorganisms in the hospital environment, especially in the center during the COVID-19 pandemic.